XPA, XPC, and XPD Modulate Sensitivity in Gastric Cisplatin Resistance Cancer Cells - Pajuelo-Lozano, Natalia; Bargiela-Iparraguirre, Jone; Dominguez, Gemma; Quiroga, Adoracion G.; Perona, Rosario; Sanchez-Perez, Isabel (Frontiers in Pharmacology, 2018)
Cisplatin is an election drug widely used in clinic for the treatment of advanced gastric cancer. However, the heterogeneity of the gastric tumors and its resistance to the drugs, make in some cases the response very low and the prognosis unpredictable. In this manuscript we aim to find the molecular processes involved in Cisplatin-induced apoptosis in two gastric cancer cell lines with different sensitivity to the treatment: AGS and MKN45. The apoptosis induction is higher in MKN45 than in AGS cells in response to CDDP. The intrinsic apoptotic pathway study revealed that MKN45 cells undergo degradation of Mcl-1 together with an increase of Bid and Bad levels, which results in sensitivity to CDDP. In addition, DNA repair NER pathway is impair in MKN45 cells due to low levels of XPC and the absence of translocation of XPA and XPD to the nucleus after stimuli. Altogether, these results suggest that NER and Bcl-2 protein family proteins are potential targets to improve the response to cisplatin treatment.